2008
DOI: 10.4161/cib.1.2.7143
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum continuity in the protozoan parasiteEntamoeba histolytica

Abstract: Entamoeba histolytica has been described as an early branching eukaryotic parasite based on the lack of organelles such as mitochondria and peroxisomes, and on morphologic studies that concluded it possesses a vesicular endoplasmic reticulum (ER) and Golgi complex. However, a recent study from our laboratory showed that the E. histolytica ER is continuous by using an ER-targeted green fluorescent protein fusion protein and photobleaching experiments. We proposed that the vesicular ER seen earlier was likely an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…An interesting aspect of the biology of E. histolytica is the absence of well-defined morphological structures corresponding to the rough endoplasmic reticulum (rER), Golgi bodies [ 36 ] or microtubular spindle [ 48 ]. However, there are protein orthologs of established eukaryotic endomembrane systems, and functional ER and Golgi can be predicted [ 49 , 50 ]; in addition, α, β, and γ tubulin have been identified but they differ significantly from other eukaryotic tubulins, sharing only 50%, 58%, and 46% identity, respectively [ 48 ]. The actin-rich cytoskeleton plays a crucial role in all life processes of E. histolytica : division, encystation, motility, endocytosis, and in other processes supporting pathogenesis, such as phagocytosis of human cells and parasite resistance to host immune responses.…”
Section: The Trophozoite As the Vegetative Cellular Form Of ...mentioning
confidence: 99%
“…An interesting aspect of the biology of E. histolytica is the absence of well-defined morphological structures corresponding to the rough endoplasmic reticulum (rER), Golgi bodies [ 36 ] or microtubular spindle [ 48 ]. However, there are protein orthologs of established eukaryotic endomembrane systems, and functional ER and Golgi can be predicted [ 49 , 50 ]; in addition, α, β, and γ tubulin have been identified but they differ significantly from other eukaryotic tubulins, sharing only 50%, 58%, and 46% identity, respectively [ 48 ]. The actin-rich cytoskeleton plays a crucial role in all life processes of E. histolytica : division, encystation, motility, endocytosis, and in other processes supporting pathogenesis, such as phagocytosis of human cells and parasite resistance to host immune responses.…”
Section: The Trophozoite As the Vegetative Cellular Form Of ...mentioning
confidence: 99%
“…The exact organisation of their membrane systems is still under investigation, but it has been suggested that their atypical membrane organisations might be interpreted as diverse TVN morphologies. They are described using various terms; Golgi-derived branching or varicose tubules, as a tubular network (although no vesicles are formed) in microsporidia [ 39 ]; ER-derived continuous reticular network in E. histolytica [ 40 , 41 ]; and a contiguous ER and endosome/lysosome compartment continuous with the nuclear envelope in G. lamblia ( Figure 2 ) [ 42 ]. The G. lamblia ES has been interpreted as “an ER-like tubulovesicular compartment, which itself can dynamically communicate with clathrin-containing vacuoles at the periphery of the cell to receive endocytosed proteins” [ 42 ].…”
Section: Our Proposalmentioning
confidence: 99%
“…There is no evolutionary relationship between those organisms, nor do we imply one with the ancestral eukaryotic ES. Those particular eukaryotic cell plans are most likely derived by reductive evolution from a complex ancestor with a ‘classical’ eukaryotic ES [ 19 , 41 , 43 ]. They are unlikely to be deep branching or ancestral.…”
Section: Our Proposalmentioning
confidence: 99%
“…Because no organelles equivalent to the Golgi apparatus had been found in E. histolytica , it was suggested that the functions were carried out in morphologically undifferentiated cytoplasmic vacuoles (Bredeston et al, 2005; Ghosh et al, 1999; Perdomo et al, 2016; Rodríguez et al, 2018; Vaithilingam, Texeira, & Huston, 2008).…”
Section: Introductionmentioning
confidence: 99%